The Impact of Intelligent Transportation System in Reliability of Bus Rapid Transit in the City of Bandung - Hadi, Prayoga Luthfil; Sutandi, Anastasia Caroline; Wasanta, Tilaka; Prasetijo, Joewono (Journal of Transportation Study Forum, 2025)
Traffic congestion is one of the main problems in large cities around the world, including in the city of Bandung, Indonesia. The congestion in Bandung is caused not only by the close distance of intersections but also by the high level of motorization. With the economic growth of the city of Bandung, the movement needs have increased to support economic activities. The lack of public transportation and the unreliability of existing public transportation have worsened the traffic congestion in Bandung. To solve this, in 2023, the Ministry of Transportation of the Republic of Indonesia promoted the implementation of bus-based public transportation in Bandung. But this bus-based public transportation needs a system that can support the reliability of this public transportation. Recognizing this issue, the implementation of an Intelligent Transportation System needs to be considered to enhance the reliability of public transportation. With the implementation of the Intelligent Transportation System, it is known that delays and the number of bus stops can be reduced, while increasing the operational speed of the buses.